Número, tipo de envases y cantidad de residuos tóxicos de plaguicidas abandonados en dos agroecosistemas de hortalizas, en Chiclayo, Perú 2007-2009 - Calderón Arias, Carmen Patricia (2010)
The main objective of this thesis was to quantify the number and identify the types and other characteristics of pesticide containers and to determine the amount (weight and volume) of the toxic waste contained in them for use in vegetable agroecosystems Monsefú ( Callancas, Monsefú) and Reque, Province of Chiclayo, Lambayeque Region from September to December 2009. Identifies three sampling areas: Callancas, Reque Monsefú and were evaluated in 62, 95, and 183 sampling units (MU) respectively. The UM was 2500 m2., In which were collected and used containers of pesticides to the farmers surveyed. UM 340 (85 hectares), were collected 413 containers used, averaging 4.54 packaging/ha. The containers were the most frequent 1000 g and 1000 ml capacity. The 88.14% of the plastic containers were collected, with the High Density Polyethylene - HDPE predominant. The mean residue weight and volume was 0.20 g /1 kg pack and 2.80 ml / 1L bottle. The volume of pesticide residue found, should be treated as "hazardous waste", as exceeds the allowable residue 0.1% (set by the EPA), having completed the triple washed. 78.9% of pesticide containers untreated triple-washed. According to surveys Monsefú practice was washed three times higher than Callancas and Reque, being in this area the lowest average residue (0.04 g / 1 kg pack. And 1.16 ml / pack of 1 L.). 53.8% of packaging waste are disposed of in the irrigation canals. Highly toxic pesticides (known as Lannate methomyl) and highly toxic (Methamidophos) in categories Ia and Ib are the most used, performing up to 20 applications per year for Licopersicum esculentum "tomato", resulting in the emergence and increase of pests (Bemisia tabaci) and diseases (Oidium sp. "oidium). The lack of training farmers Callancas, Monsefú and Reque (89.7%), is one of the causes of improper handling of containers and pesticide residues, evident that farmers did not make the practice of triple washing, did not apply Integrated Pest Management, did not use the recommended dose of pesticides, mixed three or more pesticides, and generally did not use protection suffered adverse reactions like headache when exposed to pesticidas.